Quality Control and Anti-Inflammatory Activity of the Stem Bark of Chlorophora regia A. Chev. (Moraceae): Quality Control of Herbal Products - Isaiah Amoo; James Oppong-Kyekyeku; Eric Boakye-Gyasi; Samuel Asare-Nkansah; Joseph Kwasi Adu (Journal of Tropical Pharmacy and Chemistry, 2021)
This study sought to develop a validated reverse-phase high-performance liquid chromatography method for the quality control of the stem bark ingredients and its finished products and investigate the synergistic anti-inflammatory activity of the phytochemical constituents of C. regia stem bark. Fractionation and isolation of biomarkers were carried out by column chromatography on silica gel and monitored by thin-layer chromatography. The isolated biomarkers were characterized based on their melting points and extensive analysis of their spectroscopic data (IR, 1D and 2D NMR). The chromatographic separation was investigated and developed for the analysis of the biomarkers using µBondapakTM C18 (3.9×300 mm, 5 µm) as stationary phase. The mobile phase composition of 0.1 % trifluoroacetic acid as solvent A, and methanol as solvent B with gradient elution was finally selected. The carrageenan-induced edema in a 7-day-old chick model was used to assess the anti-inflammatory activity of the stem bark extract and compared to diclofenac sodium as a reference drug. Two compounds were successfully isolated and identified, as Regiafuran A (1) and 3,5,7,4’-Tetrahydroxy-2’-methoxyflavonol (2). The compounds were employed as biomarkers in the RP-HPLC method development. The developed method was validated and was successfully used to quantify the amount of 1 and 2 in the stem bark to be 0.224% ± 0.056%w/w and 0.354% ± 0.041%w/w respectively. The crude extract showed considerable anti-inflammatory activity compared to the reference drug, diclofenac. The method demonstrated acceptable levels of accuracy, precision, specificity, and robustness hence can be successfully adopted for routine quality control and standardization of the stem bark of C. regia. The stem bark of the plant exhibited significant anti-inflammatory activity.